1988
DOI: 10.1017/s0950268800029393
|View full text |Cite
|
Sign up to set email alerts
|

Persistent enteral infections with adenovirus types 1 and 2 in infants: no evidence of reinfection

Abstract: SUMMARYIsolates of adenovirus types 1 and 2, obtained from 11 infants with prolonged faecal excretion (up to 515 days), were compared by DNA restriction analysis with seven standard endonucleases which recognize hexanucleotides and two additional endonucleases which recognize tetranucleotides. In all instances identical genome types were identified in isolates obtained early and late after infection. Our interpretation of these data is that a chronic persistent infection occurred in these children, and not a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…Subgenus C serotypes have a greater propensity to establish latency or persistent infection among the various serotypes infecting in childhood. 23 Serotype data were not available in most studies, but 2 large reviews suggested that the isolates identified in North America are mostly from subgenus B (serotypes 11, 34, 35). 4,5 We have demonstrated antiadenovirus antibodies recognizing types 2 and 5 antigens in the pretransplantation sera of both patients and donors, suggesting reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Subgenus C serotypes have a greater propensity to establish latency or persistent infection among the various serotypes infecting in childhood. 23 Serotype data were not available in most studies, but 2 large reviews suggested that the isolates identified in North America are mostly from subgenus B (serotypes 11, 34, 35). 4,5 We have demonstrated antiadenovirus antibodies recognizing types 2 and 5 antigens in the pretransplantation sera of both patients and donors, suggesting reactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Although primary infections are respiratory, species C viruses display prolonged fecal excretion months, and even years, after virus is no longer detected in nasopharyngeal washings (14,15). Restriction analysis of viruses isolated up to 4 years after initial infection suggested chronic persistent infection rather than reinfection with the same serotype (1).…”
mentioning
confidence: 98%
“…Although primary infections are respiratory, species C viruses are found in feces months, and even years, after virus is no longer detected in nasopharyngeal washings (18,19). Restriction analysis of viruses isolated years after initial infection suggests persistent infection, rather than reinfection with the same serotype (1).…”
mentioning
confidence: 99%